2023
DOI: 10.17505/jpor.2023.25265
|View full text |Cite
|
Sign up to set email alerts
|

A proof of concept study on individual trends in suicidal ideation: an ecological momentary assessment study of 5 patients over three months

Abstract: Background: Suicidal ideation (SI) is a significant and long-lasting mental health problem, with a third of individuals still experiencing SI after two years. To date, most Ecological Momentary Assessment (EMA) studies of SI have assessed its day-to-day course over one to four consecutive weeks and found no consistent trends in average SI severity over time. Aim: The current proof of concept study assessed daily fluctuations of SI over a time span of 3 to 6 months to explore whether individual trends in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additionally, EMA data on four other symptoms were collected: sad mood, feeling happy, feeling hopeless, and feeling content. Initial analysis of the long term trend of suicide ideation of five patients that completed 3 assessments a day for a period of 3-6 months found that longer-term trends of suicide ideation over time can be identified (Nuij et al, 2023). For example, two patients exhibited a steady rise in suicide ideation, while another experienced a sudden increase following a gradual decline to baseline level.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, EMA data on four other symptoms were collected: sad mood, feeling happy, feeling hopeless, and feeling content. Initial analysis of the long term trend of suicide ideation of five patients that completed 3 assessments a day for a period of 3-6 months found that longer-term trends of suicide ideation over time can be identified (Nuij et al, 2023). For example, two patients exhibited a steady rise in suicide ideation, while another experienced a sudden increase following a gradual decline to baseline level.…”
Section: Introductionmentioning
confidence: 99%